2012
DOI: 10.3892/ol.2012.832
|View full text |Cite
|
Sign up to set email alerts
|

Study of the correlation between H-ras mutation and primary hepatocellular carcinoma

Abstract: Abstract. The aim of this study was to investigate the correlation between H-ras mutation and primary hepatocellular carcinoma (HCC) and to describe the role of H-ras mutation in carcinogenesis. Clinical samples of 69 patients were collected and the expression levels of H-ras in HCC and the surrounding normal tissues were examined using HotStarTaq PCR. H-ras mutation was further analyzed using the PCR direct sequencing method. The results showed that H-ras mutation was present in 49 samples (49/69, 71.01%), of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…RAS mutations did not seem to play an important role in HCC carcinogenesis in Black Africans (Leon and Kew, 1995). Even though the mutations of RAS family genes are infrequent in Asian population (1.7-5.6% K-RAS, 0% B-RAF, 0-71% H-RAS (Harvey rats sarcoma), 0% N-RAS (rats sarcoma neuroblastoma homolog)) (Hou et al, 2014;Taketomi et al, 2013;Zuo et al, 2012;Sui et al, 2012), mutation rate seems to be higher in Western population (2-16% K-RAS, 0-23% B-RAF, 14% N-RAS) (Janku et al, 2014;Stork et al, 1991;Colombino et al, 2012;Tannapfel et al, 2003). One of the highest rate of K-RAS mutation (42%) has been described in Western workers exposed to vinyl chloride, which seems to have a direct toxic effect in the hepatocytes (Weihrauch et al, 2001).…”
Section: Ras/raf/mek/erk Pathwaymentioning
confidence: 99%
“…RAS mutations did not seem to play an important role in HCC carcinogenesis in Black Africans (Leon and Kew, 1995). Even though the mutations of RAS family genes are infrequent in Asian population (1.7-5.6% K-RAS, 0% B-RAF, 0-71% H-RAS (Harvey rats sarcoma), 0% N-RAS (rats sarcoma neuroblastoma homolog)) (Hou et al, 2014;Taketomi et al, 2013;Zuo et al, 2012;Sui et al, 2012), mutation rate seems to be higher in Western population (2-16% K-RAS, 0-23% B-RAF, 14% N-RAS) (Janku et al, 2014;Stork et al, 1991;Colombino et al, 2012;Tannapfel et al, 2003). One of the highest rate of K-RAS mutation (42%) has been described in Western workers exposed to vinyl chloride, which seems to have a direct toxic effect in the hepatocytes (Weihrauch et al, 2001).…”
Section: Ras/raf/mek/erk Pathwaymentioning
confidence: 99%
“…All experiments conformed to the Animal Care and use Guidelines of the Institute for Nutritional Sciences (Shanghai, China). Briefly, 4-to 6-week old female BALB/c athymic nude mice were obtained from Shanghai Experimental Animal Center (Shanghai, China) and subcutaneously injected with a suspension containing 5x10 6 negative control and H1-siRNA and H2-siRNA transfected cells. One week after cell implantation, DDP (4 mg/kg) was injected intraperitoneally into the tumor-bearing mice every 4 days for 3 weeks (between days 8 and 31).…”
Section: Construction Of the H-ras Shrna Vector And Gene Transfectionmentioning
confidence: 99%
“…As a result, Ras mutations can lead to the production of permanently activated Ras oncoprotein, which occurs in ~30% of all human cancers (4,5). In HCC, a recent study showed that H-Ras mutation was present in 49/69 (71.01%) of HCC patient samples (6). Overall, the mutated Ras protein leads to uncontrolled cell proliferation and resistance to apoptosis signals (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced expression or silencing of the GAPs causes increase in the levels of the GTP-bound active form of the Ras protein, leading to activated Ras-signaling in HCC. Interestingly, another study with 69 Chinese patients demonstrated mutations in H-Ras, codons 40 and 61, in about 71% of the patients (5). …”
Section: Introductionmentioning
confidence: 99%